2000
DOI: 10.1128/.74.11.5040-5052.2000
|View full text |Cite
|
Sign up to set email alerts
|

Loss of G1/S Checkpoint in Human Immunodeficiency Virus Type 1-Infected Cells Is Associated with a Lack of Cyclin-Dependent Kinase Inhibitor p21/Waf1

Abstract: Productive high-titer infection by human immunodeficiency virus type 1 (HIV-1) requires the activation of target cells. Infection of quiescent peripheral CD4 lymphocytes by HIV-1 results in incomplete, labile reverse transcripts and lack of viral progeny formation. An interplay between Tat and p53 has previously been reported, where Tat inhibited the transcription of the p53 gene, which may aid in the development of AIDS-related malignancies, and p53 expression inhibited HIV-1 long terminal repeat transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…The apoptosis of HIV-infected and bystander cells is thought to be the major cause of T-cell loss (Selliah and Finkel, 2001;Bell and Dockrell, 2003). However, emerging data suggest that HIV also developed mechanisms blocking and delaying the programmed cell death, increasing cell survival as well as activating cell proliferation (Fackler and Baur, 2002;Choi and Smithgall, 2004) with a particularly important role for Tat (Clark et al, 2000;Corallini et al, 2002;Deregibus et al, 2002;Chauhan et al, 2003;Bergonzini et al, 2004;Chipitsyna et al, 2004). In fact, it may be beneficial for HIV to inhibit apoptosis until high levels of progeny viruses are produced (Selliah and Finkel, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The apoptosis of HIV-infected and bystander cells is thought to be the major cause of T-cell loss (Selliah and Finkel, 2001;Bell and Dockrell, 2003). However, emerging data suggest that HIV also developed mechanisms blocking and delaying the programmed cell death, increasing cell survival as well as activating cell proliferation (Fackler and Baur, 2002;Choi and Smithgall, 2004) with a particularly important role for Tat (Clark et al, 2000;Corallini et al, 2002;Deregibus et al, 2002;Chauhan et al, 2003;Bergonzini et al, 2004;Chipitsyna et al, 2004). In fact, it may be beneficial for HIV to inhibit apoptosis until high levels of progeny viruses are produced (Selliah and Finkel, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it has been reported that, while Tat induces apoptosis in uninfected T cells in peripheral blood, it decreases apoptosis in HIV-1-infected T cells (McCloskey et al, 1997;Lum and Badley, 2003). In fact, the loss of the G 1 /S checkpoint may provide a selective advantage for HIV by allowing virus transcription and virion production, which require T-cell cycling (Clark et al, 2000). Tat appears to play an important role in this particular process by inactivating the p53 pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction sites were found to be AA 341–355 in p53, corresponding to the NES in the tetramerization domain, and AA 49–57 in the ARM domain of Tat 15. The C‐terminal part of p53, which includes the tetramerization domain, was shown to bind Tat specifically 30. Subsequent in vivo studies demonstrated that AA 73–86 of Tat bind p53 indirectly, and that the interaction is mediated by cellular proteins 16.…”
Section: Introductionmentioning
confidence: 98%
“…P53 is upregulated by cellular stress and noxious injury and is an important inhibitor of cell cycle progression at numerous check points throughout the cell cycle (20). Clark et al demonstrated that the HIV-1 Tat interaction with p53 results in the loss of p21/Waf1 inhibition of cyclin E-cdk2 activation (21). A potential consequence of these events is the preferential entry of HIV-1-infected cells into S phase, where viral replication can proceed, as has been suggested by others (7).…”
mentioning
confidence: 99%